2019
DOI: 10.3390/su11082328
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Brownfield Sites on Local Energy Production as Resilient Response to Land Contamination: A Case Study in Italy

Abstract: The decentralization of the production sector crisis following industries in the suburbs have generated a multitude of empty containers in the medium-large Italian cities, which are abandoned, unsafe, and often dangerous for the community. From this arises the need to recover them and transform them into something else. This is not always possible or interesting for the subjects involved in the transformation. When the abandoned space is (even if only partially) polluted, then any hypothesis of transformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Finally, tax incentives, which are the subject of analysis in this paper, often offered in the form of income tax incentives or VAT reductions, are active in Belgium, Denmark, Finland, France, Italy, Malta, Sweden, the Netherlands, and the United Kingdom. In line with these initiatives, we observed that the Italian government is introducing different tax-building incentives to response to the government's courses of action toward the efficient upgrading of Italy's ageing residential real estate stock [8]. In this sense, this makes a series of incentive tools available to private individuals to carry out renovation (and other) interventions on their residential properties.…”
Section: Theoretical Evaluation Frameworkmentioning
confidence: 94%
See 1 more Smart Citation
“…Finally, tax incentives, which are the subject of analysis in this paper, often offered in the form of income tax incentives or VAT reductions, are active in Belgium, Denmark, Finland, France, Italy, Malta, Sweden, the Netherlands, and the United Kingdom. In line with these initiatives, we observed that the Italian government is introducing different tax-building incentives to response to the government's courses of action toward the efficient upgrading of Italy's ageing residential real estate stock [8]. In this sense, this makes a series of incentive tools available to private individuals to carry out renovation (and other) interventions on their residential properties.…”
Section: Theoretical Evaluation Frameworkmentioning
confidence: 94%
“…In this sense, there is a situation in which the private investor should be invested with a greater responsibility toward the creation of use value linked not only to the satisfaction of their own needs but also those of society and the environment in which the latter is embedded. This increase in responsibility could be repaid by positive economic implications for the investor, for example, by increasing the market value of the artefact [3,8]; however, this may not be sufficient to persuade the investor to pursue sustainable transformations. As [9] reports, instruments such as grants, subsidies, and tax breaks can be used to stimulate private sector involvement in the implementation of urban development projects, as they can reduce investment risks and accelerate the return on investment [9].…”
Section: Introductionmentioning
confidence: 99%
“…There are various brownfield case studies, international [27][28][29] and regional [30,31], with positive and negative implications, but also numerous dilemmas in the context of sustainability. Previous research into successful examples of the particular water-front brownfield regenerations of post-industrial cities [32] and different methodological approaches vary depending on the specific environment and cases [33,34]. In particular, the authors point to the inadequate integration of sustainable development goals into practice [35].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Sustainable urban development constitutes a global goal (Wang & Peng, 2020). Cities, as representative of crucial nodes of action for development, see the concept of sustainability as a lens through which one can conceptualise different environmental, economic and social challenges in urban and architectural design for both new developments and reuse of abandoned sites and buildings (Mecca et al, 2019; Quaglio et al, 2021; Schroeder, 2018): it is indeed translated into specific practices that enable its materialisation.…”
Section: Introductionmentioning
confidence: 99%